Temperature-independent refractometer based on fiber-optic Fabry–Perot interferometer. (April 2016) - Li, Jiacheng; Qiao, Xueguang; Wang, Ruohui; Rong, Qiangzhou; Bao, Weijia; Shao, Zhihua; Yang, Tingting
Abstract: A miniature fiber-optic refractometer based on Fabry–Perot interferometer (FPI) has been proposed and experimentally demonstrated. The sensing head consists of a short section of photonics crystal fiber (PCF) spliced to a single mode fiber (SMF), in which the end-face of the PCF is etched to remove holey structure with hydrofluoric (HF) acid. A Fabry–Perot interference spectrum is achieved based on the reflections from the fusion splicing interface and the end-face of the core of PCF. The interference fringe is sensitive to the external refractive index (RI) with an intensity-referenced sensitivity of 358.27 dB/RIU ranging from 1.33 to 1.38. The sensor has also been implemented for the concentration measurement of λ-phage DNA solution. In addition, the dip intensity is insensitive to the ambient temperature variation, making it a good candidate for temperature-independent bio-sensing area. Highlights: A miniature sensing structure with a length of ~150 μm is proposed. The fabrication process only includes fusion and etching. RI and temperature response are characterized by monitoring the interference dip change. Simultaneous measurement for RI and temperature has been achieved. This sensor has been proved to be a good candidate for bio-sensing applications.